2008
DOI: 10.1021/ja803507d
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective Colorimetric and Visual Detection of Nucleic Acids Using an Asymmetrically Split Peroxidase DNAzyme

Abstract: G-quadruplex containing peroxidase DNAzyme is a complex of hemin and a single-stranded guanine-rich DNA (hemin-binding DNA aptamer), which is used as an attractive catalytic label for biosensing recently. Therein, the hemin-binding DNA aptamer contains four GGG repeats and can fold into a G-quadruplex structure. In this paper, we have developed a new split mode to divide the hemin-binding DNA aptamer into two parts: one possesses three GGG repeats, and another part possesses one GGG repeat, namely, the 3:1 spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
178
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(181 citation statements)
references
References 26 publications
2
178
1
Order By: Relevance
“…Zhang and Winfree have shown that single-nucleotide mutations, insertions, and deletions in the catalyst strand can result in 10-to 300-fold reductions in its efficiency in catalyzing strand exchange [17]. These reductions in signal observed with single-nucleotide mismatches are comparable to other well-developed DNA sensors [26][27][28][31][32][33]. Consistent with these findings, we observed that when a single nucleotide was changed in the toehold region (Figure 3, inset), the mutant Trigger did not yield any peroxidase activity above background even at 150 nM concentration ( Figure 3, sample #10~12).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Zhang and Winfree have shown that single-nucleotide mutations, insertions, and deletions in the catalyst strand can result in 10-to 300-fold reductions in its efficiency in catalyzing strand exchange [17]. These reductions in signal observed with single-nucleotide mismatches are comparable to other well-developed DNA sensors [26][27][28][31][32][33]. Consistent with these findings, we observed that when a single nucleotide was changed in the toehold region (Figure 3, inset), the mutant Trigger did not yield any peroxidase activity above background even at 150 nM concentration ( Figure 3, sample #10~12).…”
Section: Resultsmentioning
confidence: 86%
“…We also demonstrate that an entropy-driven catalytic DNA circuit can function as a generic signal amplification module that allows lower concentrations of input molecules to control the production of higher concentrations of deoxyribozymes, and thus exceed the limit of stoichiometric allosteric control. The system is qualitatively sensitive to mismatches in the input nucleic acid, suggesting that the combined entropy-driven strand exchange and allosteric deoxyribozyme circuit might facilitate the future development of enzyme-free, point-of-care diagnostic assay system [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…In the detection system, the initial tool for SNP analysis is the molecular-beacon probe (19); however, the requirement for the instrument and the individually fluorescence-labeled probe is definitely costly. The peroxidase DNAzyme was selected due to its robustness, its sensitivity, and its relatively low cost (3,12,14,25,26,27,32). Here, we apply the 3:1 split DNAzyme to detect target DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This method was further extended and, by combining with a personal glucose meter, a quantitative detection system of non-glucose targets was developed. 326,354 By entrapping gold nanoparticles in aptamer-based DNA hydrogels, proteins were also detected with a very high sensitivity. 355 When the target protein was recognized by the aptamer in the gel, the gel was broken down and the gold nanoparticles were released to the solutions.…”
Section: Sensing In Vivo and In Vitromentioning
confidence: 99%